The impact of the costs of subscription on measured IPO returns: the case of Asia - Fung, Joseph K.W; Cheng, Louis T.W; Chan, Kam C (Journal of Corporate Finance, 2004)
Asian initial public offerings (IPOs) require investors to pay subscription funds up-front upon submission of applications, and these funds are locked-up for 1–3 weeks without interest. Hence, the IPO process entails an explicit financing cost (opportunity cost) whether investors borrow funds or use their own funds to apply for IPO shares. The IPO subscription costs are not trivial, especially in a high interest rate environment or when an IPO is highly oversubscribed. These costs should be considered in any comparison of IPO returns across countries.